Behavior and shear strength of steel shape reinforced concrete deep beams. (15th November 2018) - Chen, Cheng-Cheng; Lin, Keng-Ta; Chen, Yu-Jen
Highlights: The depth of the steel shape may affect the shear strength of the SRC deep beams. The SRC deep beams possessed more ductile behavior than the RC deep beams did. The SST model was modified to capture the shear strength of SRC deep beams. Abstract: The shear behavior of steel reinforced concrete (SRC) deep beams was investigated, and an analytical model for predicting the shear strength of SRC deep beams was developed. A total of 12 deep beams were fabricated and tested to failure to study shear behavior. The tests revealed the following: (1) the wide flange shape may contribute considerably to the shear strength of the SRC deep beams; (2) the depth of the wide flange shape may affect the shear strength of the SRC deep beams; and (3) the SRC deep beams possessed more ductile behavior than the RC deep beams did. The softened strut-and-tie (SST) model for predicting the shear strength of RC deep beams was modified to accommodate the effect of wide flange shapes on the shear strength of SRC deep beams. The modified model, called SST-SRC, could capture the shear behavior of the fabricated SRC deep beams.